COMPRESSION ONLY LIFE SUPPORT (COLS) CARDIOPULMONARY RESUSCITATION TRAINING IN SCHOOL AND ITS INTRODUCTION IN SCHOOL CURRICULUM: A STUDY PROTOCOL - Dr. Kirti Gujarkar; Dr Alka Rawekar; Dr. Anjali Borkar; Dr. Pratibha Deshmukh; Dr. Prajwal Mahatme (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Immediate cardiopulmonary resuscitation, or CPR, greatly improves survival rates and chances in cases of sudden cardiac arrest, which is one of the world's major causes of morbidity and mortality. Compression Only Life Support (COLS) is a simplified CPR method recommended for laypersons, especially in resource-limited settings. Introducing COLS training at the school level empowers students with lifesaving skills.Objective: Study will assess the knowledge and attitude in school children about COLS. Also will teach school children and teachers about compression only lifesupport CPR. Study objective includes introduction of cols protocol in school curriculum.Methods: This is a mixed - methods, prospective, interventional study conducted across schools. The study includes teacher training, student workshops, pre-training and post-training assessments and curriculum development. Quantitative data will be collected through structured questionnaires, while qualitative feedback from students, and teachers.Expected Outcomes: The study anticipates that COLS training will significantly improve students’ understanding and practical ability in performing CPR. Findings will inform policy recommendations for incorporating CPR training into school curriculum.Conclusion: Equipping students with COLS CPR training through school-based programs has the potential to create a generation of first responder. This protocol sets the foundation for large-scale implementation and policy-level integration of lifesaving education in schools.